Appearance of Zahiriddin Muhammad Bobur in "Boburnoma" - Nizomovich, Aslonov Ilhom (Central Asian Journal of Theoretical and Applied Science, 2022)
Boburnoma is a major memoir covering the history of Central Asia, Afghanistan, Iran and India in the late 15th and early 16th centuries. In the play, the image of Babur appears not only as an observer of historical events, but also as a direct participant, and the work becomes a reliable source for obtaining extensive information about the author.